Size and Depth of Vocabulary Knowledge: What the Research Shows. Issue 4 (16th October 2014) - Schmitt, Norbert
<x xml:space="preserve">Abstract</x> When discussing vocabulary, a distinction is often made between size of vocabulary (number of known words) and depth of knowledge (how well those words are known). However, the relationship between the two constructs is still unclear. Some scholars argue that there is little real difference between the two, while regression analyses show that depth typically adds unique explanatory power compared to size alone. Ultimately, the relationship between size and depth of vocabulary knowledge depends on how each is conceptualized and measured. In an attempt to provide an empirical basis for exploring the size–depth relationship, this critical synthesis identifies studies that contain measures of both size and depth. Based on a number of different conceptualizations of depth, various patterns emerged. For higher frequency words and for learners with smaller vocabulary sizes, there is often little difference between size and a variety of depth measures. However, for lower frequency words and for larger vocabulary sizes, there is often a gap between size and depth, as depth measures lag behind the measures of size. Furthermore, some types of word knowledge (e.g., derivative knowledge) seem to have generally lower correlations with size than other types.